AKUISISI BANK DIGITAL ASING E-COMMERCE SHOPEE DITINJAU DARI MAQA>SID AL-SHARI>‘AH DAN HUKUM POSITIF (STUDI KASUS PADA PT. SEABANK INDONESIA ATAS BANK KESEJAHTERAAN EKONOMI - Masadah, Masadah; fageh, achmad; najah, Ahmadun (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2023)
Implementing the acquisition of foreign digital bank SeaBank Indonesia over Bank Kesejahteraan Ekonomi (Bank BKE) Bis based on the regulations of Law Number 40 of 2007 concerning Limited Liability Companies Article 125, Article 135. Banking Law No. 10 of 1998 on the licensing of foreign persons and institutions establishes and owns up to 90% of shares in national banks., Decree No. AHU-0002728. Ah.01.02 of 2021 issued by the Minister of Law and Human Rights of the Republic of Indonesia on January 15, 2021, concerning Approval of Amendments to the Articles of Association of Limited Liability Companies of PT Bank Seabank Indonesia. ; Decree No. KEP-12/PB.1/2021 issued by the Deputy Commissioner of Banking Supervision I of the Financial Services Authority dated February 10, 2021, concerning the Determination of the Use of Business Licenses on Behalf of PT Bank Kesejahteraan Ekonomi into a Business License on Behalf of PT Bank Seabank Indonesia. ; Letter No. S-32/PB.33/2021 issued by the Head of Bank Supervision Department 3 of the Financial Services Authority dated February 17, 2021, concerning Changes in the Bank's Logo. SeaBank Indonesia's acquisition of a foreign digital bank for Economic Welfare Bank (Bank BKE) is essentially an acquisition in the form of shares. Buying and selling shares that have fulfilled the pillars and conditions of buying and selling according to the muamalah; ijab, and qabul are characterized by cash ad carry. Ijab-Kabul buying and selling can be done orally, written, or by messenger.; Both parties have full authority to carry out legal actions (adult and professional); The Maqa>sid al-Shari>'ah approach to the practice of SeaBank Indonesia's acquisition of the Foreign Digital Bank of the Economic Welfare Bank (Bank BKE) is essentially essential because the products invested are not contrary to human nature and maslahat. Macroeconomically, this practice has met stakeholders' interests, such as sellers, buyers, etc. It is qualified that it must not conflict with the human benefit or Maqa>sid al-Shari>' ah (purpose of Islamic law).